Asymmetric cipher protocol using conjugacy and discrete logarithm problem - Raulynaitis, Andrius; Venclovienė, Agnė (Lietuvos matematikos rinkinys, 2009)
The paper proposes asymmetric cipher protocol based on matrix field over some field F. The asymmetric cipher is based on two simultaneous problems: matrix conjugator search problem (MCSP) and matrix discrete logarithm problem (MDLP). The algorithm construction does not allow performing a crypto-analysis by replacing the existing MCSP solution to the matrix decomposition problem (MDP) solution. The security parameters are defined and preliminary security analysis is presented.